Enhancing the Capacity of Santri During the COVID-19 Pandemic at Pesantren - Arofik, Slamet; Fitri, Abdul Basit Misbachul (Bisma : Bimbingan Swadaya Masyarakat, 2023)
The impact of the Covid-19 pandemic resulted in all activities in life seemingly stopping. Among the activities and activities affected by Covid-19 are all access to life including educational institutions ranging from the lowest level to higher education. All educational institutions are not allowed to conduct teaching and learning activities freely but with limited. Therefore STAI Darussalam Nganjuk set PKM by means of PKM-KPM DRP. As an assisted partner is Yayasan Islam al-Ghozali (YIGA) Krempyang Tanjunganom Nganjuk and working group (POKJA) 10 chose and set Pondok Pesantren Putra Miftahul Mubtadiin Ar-Ridlo as an assisted partner. The mentoring approach/method used is ABCD (Asset Bassic Community Development). The purpose of mentoring includes three things, namely Strengthening the Capacity of Moderators Takror and Bahsul Masail, Publishing Diktat Kitab al-Barzanji and Strengthening the Capacity of Administrators and Caregivers of Children's Students. The result of the dedication is the ABCD Approach is able to deliver assisted partners experiencing capacity building. Each of the focus assistance is able to increase by 30 to 50%.